Math Doubts

Solve $\dfrac{x-3}{5}-2 = -1$ by Inverse Operations Method

$\dfrac{x-3}{5}-2 = -1$ is an equation in terms of a variable $x$. In this algebraic equation, the power of the variable $x$ is one and no other variable is involved. So, it is a linear equation in one variable and it can be solved systematically by the inverse operations method.

Eliminate -2 from expression by Addition

$\dfrac{x-3}{5}-2 = -1$

In left-hand side of the equation, the two terms are connected by subtraction. It is essential to eliminate $-2$ from this expression and it can be done by adding $2$ to both sides of the equation.

$\implies$ $\dfrac{x-3}{5}-2+2$ $=$ $-1+2$

$\implies$ $\require{cancel} \dfrac{x-3}{5}-\cancel{2}+\cancel{2}$ $=$ $1$

$\implies$ $\dfrac{x-3}{5} = 1$

Eliminate 5 from expression by Multiplication

$\dfrac{x-3}{5} = 1$

The number $5$ is dividing the algebraic expression $x-3$ in the left-hand side of the equation. It can be eliminated from this expression by multiplying both sides of the equation by $5$.

$\implies$ $5 \times \Bigg[\dfrac{x-3}{5}\Bigg]$ $=$ $5 \times 1$

$\implies$ $\dfrac{5(x-3)}{5}$ $=$ $5$

$\implies$ $\require{cancel} \dfrac{\cancel{5}(x-3)}{\cancel{5}}$ $=$ $5$

$\implies$ $x-3 = 5$

Eliminate -3 from expression by Addition

$x-3 = 5$

Two terms are connected by subtraction in the left-hand side of the equation. For solving $x$, the number $-3$ should be eliminated from this expression. It can be done by adding $3$ to both sides of the linear equation.

$\implies$ $x-3+3 = 5+3$

$\implies$ $x-3+3 = 8$

$\,\,\, \therefore \,\,\,\,\,\,$ $x = 8$



Math Doubts
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more